Peran Lingkungan Sosial terhadap Pembentukan Karakter Anak Usia Dini di Jogja Green School - Shofiyatuz Zahroh; Na'imah Na'imah (Universitas Trunojoyo Madura, 2020)
This study aims to examine the role of the environment on the formation of children's character in Jogja Green School. The research method used is qualitative with a case study approach. Data collection techniques used interviews with school principals and class teachers, observations of children in Caterpillar A and Caterpillar classes as well as documentation studies such as daily plain activity, weekly plain activity, daily notes, and children's work documented in the classroom. Data analysis techniques with data reduction, then all data are presented with perfect and good exposure, and make conclusions and verify data. The results showed that the social environment significantly influenced the formation of children's character through learning strategies and methods. Jogja Green School together with parents and the community creates a conducive environment in forming good character of children. The school always communicates with the family through diary or meet directly related to the child's development, so parents understand that the education provided at home must be in accordance with the education available at the school, besides that the school or family has the task of providing stimulus to the community. The community does not teach children with negative words, does not scold the child when the child accidentally destroys neighboring plants but rather gives an understanding to the child, so the child must apologize when making a mistake.